Digital financial inclusion: a bibliometric analysis of global research patternsand impacts (2005-2022) - Yahya, Mohamed Hisham; Jin, Liu A; Saidin, Saidatunur Fauzi (Kuey, 2024)
In a world increasingly characterized by rapid digital transformation, digital financial inclusion (DFI) has emerged as a critical tool for bridging economic disparities and fostering accessible financial services. This bibliometric analysis investigated 790 DFI-related papers from 2005 to 2022, aiming to elucidate the evolving landscape of DFI and its intersection with environmental sustainability. The study methodically maps the field’s growth, identifying key geographic and thematic patterns that reveal the burgeoning role of technology in emerging markets as well as the different foci on developed and developing nations. The findings indicate a concentrated drive towards digitalization in financial services within countries such as China and India, highlighting the potential of digital finance to spur economic development and reduce inequality. However, the analysis also points to a research divide, with advanced economies leading the discourse on financial inclusion’s integration into the digital economy. Despite this study’s limitations in terms of data representation and emphasis on quantitative metrics, its robust insights serve as a foundation for further exploration into the practical outcomes of DFI. Notably, the study offers a critical lens through which academics and policymakers can navigate the digital financial ecosystem to foster inclusive growth and resilience in the post-pandemic world.